Social stratification and social movements theoretical and empirical perspectives on an ambivalent relationship - Zajak, Sabrina 1980-; Haunss, Sebastian (The mobilization series on social movements, protest, and culture, 2020)
"This volume takes up the question of the connection between social movements and societal structures, addressing the neglect in social movement studies of the role of social stratification as a reason or cause for protest. Exploring the link between protest mobilization and social stratification, it challenges the assumption that with regard to social inequality, social movements are expressions of antagonistic class interests. Presenting case studies that put the European experience of social mobilization into broader, comparative perspective, Social Stratification and Social Movements connects social stratification to the emergence of protest, and its impact on the structure of society thus contributing to the development of theory dealing with the evolution and consequences of social movements"--